Do we need a strong captain to navigate the COVID-19 pandemic? Social identification, conspiracy theory beliefs, and the wish for a strong leader - Moscatelli, Silvia; Graziani, Anna Rita; Botindari, Lucia; Ciaffoni, Stefano; Menegatti, Michela (Frontiers in Psychology, 2023)
In times of great uncertainty and hardship, calls for a strong leader tend to arise. The present study delved into this issue by examining possible sociopsychological antecedents of the wish for a strong leader during the COVID-19 crisis. To this end, we explored the role of social identification, belief in conspiracy theories related to COVID-19, and trust in various relevant social actors in a sample of Italian citizens (N = 350). Results of structural equation modeling analyses showed that identification with Italians was related to a lower wish for a strong leader through the mediation of trust. Identification with Europeans had a direct and negative association with the wish for a strong leader. Finally, greater endorsement of conspiracy beliefs was related to a greater wish for a strong leader, directly and through diminished trust. These findings suggest that belief in conspiracy theories might drive individuals to depart from democratic principles, whereas relying on meaningful social identities can effectively contrast possible authoritarian turns brought about by a global societal crisis, such as the coronavirus outbreak.